Analysis of Thermal Behaviour in the Active Layer of Degrading Mountain Permafrost. (29th December 2014) - Zhou, Xiaohai; Buchli, Thomas; Kinzelbach, Wolfgang; Stauffer, Fritz; Springman, Sarah M.
Abstract Mountain permafrost is highly susceptible to the effects of climate warming, because its thermal regime is close to 0 °C. This can be evidenced by the acceleration of average annual creep rates of several rock glaciers in the Swiss Alps, whereby some exhibit even more extreme signs of degradation. Measurements obtained from a borehole drilled from a relatively flat area on a rock glacier, below the Furggwanghorn peak, Turtmanntal (Switzerland), showed positive mean annual values of ground temperatures in the active layer over two hydrological years, from 1 October 2010 to 30 September 2012. The thermal conditions in this borehole were much warmer than those measured at the same time in other boreholes in the same rock glacier. A test pit excavated in the active layer close to this borehole, and instrumented with thermistors, indicated similar thermal conditions. It was hypothesised that the thick snow cover that accumulated on the flat area during winter and an existing supra‐permafrost talik were responsible for the warm thermal regime, given the relevant meteorological inputs over this period. The degradation of the rock glacier in this flat area was probably driven by a high summer heat flux into the rock glacier, which could not be reversed in winter due to a thick insulating snow layer that accumulated from October onwards. A coupled one‐dimensional numerical model, based on SNOWPACK and HYDRUS, was developed to interpret the thermal behaviour in the active layer. The resulting numerical analysis was validated, showing that the simulated ground temperatures agreed well with measured values at various depths. The heat loss from the ground was found to be very small during the winter, due to insulation by autumnal snowfalls, whereas the heat flux to the ground had been relatively high in recent summers. The mean positive heat flux to the supra‐permafrost talik was calculated to be 1.75 Wm‐2 over the 2 year period, which is sufficient to cause considerable ice melt. Furthermore, water flow in the supra‐permafrost talik appeared to limit temperature variations in the active layer to 0.12 °C in summer. Copyright © 2014 John Wiley & Sons, Ltd.